Molecular clonality analysis of esophageal adenocarcinoma by multiregion sequencing of tumor samples - Anna M. J. van Nistelrooij; Ronald van Marion; Linetta B. Koppert; Katharina Biermann; Manon C. W. Spaander; Hugo W. Tilanus; J. Jan B. van Lanschot; Bas P. L. Wijnhoven; Winand N. M. Dinjens (BMC Research Notes, 2017)
Abstract Background Intratumor heterogeneity has been demonstrated in several cancer types, following a model of branched evolution. It is unknown to which extent intratumor heterogeneity is applicable to esophageal adenocarcinoma. Therefore the aim of this study was to characterise intratumor heterogeneity in esophageal adenocarcinoma. Methods Multiregional targeted sequencing of four commonly altered genes was performed on 19 tumor regions collected from five esophageal adenocarcinomas. Alterations were classified as homogeneous or heterogeneous based on mutational and loss of heterozygosity analysis. Results Identical TP53 mutations and homogeneously loss of heterozygosity of the TP53 locus were identified in all separated tumor regions in each of five adenocarcinomas, and in the corresponding Barrett’s esophagus and tumor positive lymph node of one primary tumor. Loss of heterozygosity of the P16 locus was homogeneous among all tumor regions in four adenocarcinomas, and an identical pattern of loss of heterozygosity was present in the Barrett’s esophagus. Loss of heterozygosity of the SMAD4 and APC loci was observed in a heterogeneous pattern. Conclusions Known driver alterations, such as TP53 and P16 are homogeneously present within each adenocarcinoma, and therefore occur early during carcinogenesis and subsequently clonally expand throughout the entire tumor. However, loss of heterozygosity of the SMAD4 and APC loci shows a heterogeneous pattern, indicating intratumor heterogeneity of esophageal adenocarcinoma.